Research-Based Learning: An Interpretive Study - Laily, Nujmatul; Rohimatullah, Dewi Noor Fatikhah; Muhammad, Muhammad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p05, 2020)
This research aimed at understanding lecturers and students’ views on research-based learning (RBL) in accounting. This was a qualitative study with interpretive paradigm. The data were obtained observation, interview and documentation. Meanwhile, the stages to analyze the data included data reduction, understanding, and interpretation. The research result showed that lecturers had varied understanding on research-based learning. The research result also indicated the minimum use of RBL by lecturers in their teaching since the course was less compatible in terms of its characteristics with RBL model. An important finding in this research was that RBL could improve student’s critical thinking and creativity as well as increase their confidence in writing scientific paper. However, as acknowledged by the informants themselves, it was hard to implement RBL since it demanded a huge amount of costs and the lecturer’s own ability to implement RBL was still low. Keywords:   accounting, RBL, critical thinking